1996
DOI: 10.3109/01902149609046037
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Allelic Distribution at the Human Pulmonary Surfactant Protein B Gene Locus (SP-B)

Abstract: Variable numbers of composite repetitive motifs are found in different individuals within intron 4 of the surfactant protein B (SP-B) gene (Biochem J. 1995;305:583). This study tests the hypothesis that the distribution of SP-B alleles differs among racial/ethnic groups. A total of 412 SP-B alleles were analyzed: 206 from Caucasian, 68 from African-American, and 138 from Nigerian individuals. Twelve groups of alleles (A-L) carrying 3 to 18 motifs were found. The distribution of the 12 alleles in the Caucasian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 12 publications
1
20
0
4
Order By: Relevance
“…The variability within intron 4 of the surfactant protein B gene is caused by the gain or loss of motifs Veletza et al, 1996), consisting of a 20 bp conserved sequence followed by various dinucleotide repeats (CA-repeats). Currently, it is not known whether the intron 4 variability has an impact on SP-B gene expression or regulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variability within intron 4 of the surfactant protein B gene is caused by the gain or loss of motifs Veletza et al, 1996), consisting of a 20 bp conserved sequence followed by various dinucleotide repeats (CA-repeats). Currently, it is not known whether the intron 4 variability has an impact on SP-B gene expression or regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR were performed as hot-start PCR with following cycling conditions: 30 cycles of 948C for 30 s, 598C for 1 min, 728C for 1 min, and a final cycle of 5 min for 728C. As a size marker we used cloned and sequenced intron 4 fragments as described previously Veletza et al, 1996). The PCR-products and the clones were analysed by 1.5% agarose gel electrophoresis and stained with ethidium bromide.…”
Section: Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variants in intron 4 are in linkage disequilibrium with genotype at a common non-synonymous (Thr131Ile) single nucleotide polymorphism (C1580T, dbSNP reference Rs1130866) (Haataja, et al, 2000). In premature infants, genetic variant alleles have been associated with increased risk for respiratory distress independently, through interaction with alleles of the 2 surfactant protein A genes, and through interaction with race and gender Haataja, et al, 2000;Hallman, 2004;Kala, et al, 1998;Liu, et al, 2003;Makri, et al, 2002;Veletza, et al, 1996). In adults, genetic variants have been associated with increased risk of acute respiratory distress syndrome, chronic obstructive pulmonary disease, interstitial pulmonary fibrosis, and squamous cell carcinoma of the lung Lin, et al, 2000;Seifart, et al, 2002a;Seifart, et al, 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Some descriptions about the presence of polymorphisms and mutations in genes from the surfactant components are reported in the literature, particularly regarding the SP-B gene, which seems to be associated with RDS, ARDS, and CAP. [34][35][36][37][38][39][40] The inability to produce SP-B is the result of an autosomic recessive disease that leads to a fatal respiratory insufficiency, congenital alveolar proteinosis (CAP), indicating the fundamental role this protein plays in normal pulmonary function. 41 In 1994, Nogee et al 42 demonstrated the existence of a mutation-type frameshift, consisting of the substitution of a nucleotide sequence, GAA, with a single nucleotide, C, on codon 121 of the gene responsible for the production of SP-B.…”
Section: Surfactant Proteins: Genetic Determinants and Pulmonary Disementioning
confidence: 99%